Antioxidant capacity and UPLC–PDA ESI–MS polyphenolic profile of Citrus aurantium extracts obtained by ultrasound assisted extraction - Ana, Covarrubias-Cárdenas (J Food Sci Technol, 2018)
This study aimed to evaluate different pre-treatments and solvent ratios on the total phenolic content and antioxidant activity of Citrus aurantium (sour orange) peel extracted by ultrasound. A two-factor (2 × 3) factorial design was implemented, with fresh and dry peels as pre-treatment conditions, and water (100%), 50% aqueous ethanol (v/v) and 96% aqueous ethanol (v/v) as the solvents. The phenolic compounds were identified and quantified by ultra-performance liquid chromatography–photodiode array and electrospray ionisation–mass spectrometry, respectively. The compounds were partially purified by advanced automated flash purification. The results indicated that the maximal phenolic content (40.95 ± 3.44 mg gallic acid equivalents/g dry weight) was obtained when fresh sour orange peels were extracted with 50% (v/v) aqueous ethanol while the maximal antioxidant activity (730.04 ± 28.60 μmol Trolox equivalents/g dry weight) was achieved from aqueous extraction of dry sour orange peels. Nine phenolic compounds were identified and quantified. Naringin and neohesperidin predominated in sour peel extracts, whereas, caffeic and chlorogenic acids were the least abundant. Evaluation of the antioxidant activity in the fractions suggested that this activity might be attributed to the synergistic effect of the nine phenolic compounds present in the crude extract. Accordingly, sour orange peel is a potential source of phenolic compounds with antioxidant activity. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-018-3451-0) contains supplementary material, which is available to authorized users.